Reconstructing Learning Culture in Contemporary Islamic Boarding Schools: Classical Text Literacy Practices among Early-Generation Students - Durroh Asyiqoh; Umar Manshur; Abdullah Abdullah; Badrul Mudarris (ISTIFHAM, 2025)
This study aims to examine how learning culture is reconstructed through classical Islamic text literacy practices among early-generation students in modern Islamic boarding schools. It employs a qualitative case study design to gain an in-depth understanding of the phenomenon within its natural context. Data were collected through observations, in-depth interviews with teachers and students, and documentation, and were analyzed using data condensation, data display, and verification techniques. The findings reveal that the reconstruction of learning culture is achieved through the integration of traditional methods such as bandongan and sorogan with interactive and contextual learning approaches, supported by adaptive teacher roles and the use of learning media. These practices significantly improve students’ literacy skills, participation, and confidence in engaging with classical texts. The study implies that combining traditional Islamic scholarship with modern pedagogical strategies can enhance the relevance and effectiveness of pesantren education.